Endosomal microdomains: Formation and function. (August 2020) - Norris, Anne; Grant, Barth D.
Abstract: It is widely recognized that after endocytosis, internalized cargo is delivered to endosomes that act as sorting stations. The limiting membrane of endosomes contain specialized subregions, or microdomains, that represent distinct functions of the endosome, including regions competing for cargo capture leading to degradation or recycling. Great progress has been made in defining the endosomal protein coats that sort cargo in these domains, including Retromer that recycles transmembrane cargo, and ESCRT (endosomal sorting complex required for transport) that degrades transmembrane cargo. In this review, we discuss recent work that is beginning to unravel how such coat complexes contribute to the creation and maintenance of endosomal microdomains. We highlight data that indicates that adjacent microdomains do not act independently but rather interact to cross-regulate. We posit that these interactions provide an agile means for the cell to adjust sorting in response to extracellular signals and intracellular metabolic cues.